Pengaruh Profitabilitas, Ukuran Perusahaan, dan Reputasi KAP Terhadap Audit Delay - Nugroho, Adnan Wisnu; Zakaria, Adam; Nasution, Hafifah (LPPM Universitas Negeri Jakarta, 2023)
This research aims to determine the effect of profitability, company size, and KAP reputation on audit delay. This research uses cyclical consumer sector companies on the main listing listed on the Indonesia Stock Exchange in 2021-2022 as the population. The data in this study were processed using the SPSS version 26 application and analyzed using multiple linear regression analysis. The sample was selected using a purposive sampling method which resulted in 76 total observations. The results of this research indicate that profitability has a negative effect on audit delay. Meanwhile, company size and KAP reputation have no effect on audit delay.